Mineralogical characteristics of arsenopyrite and pyrite in Bo Va and Nam Quang gold-sulfide deposits (Northeast Vietnam) - Huong, Ngo Thi; Hoa, Tran Trong; Anh, Tran Tuan; Dung, Pham Thi; Ly, Vu Hoang (Vietnam Journal of Earth Sciences, 2016)
Crystal morphology and chemical composition of arsenopyrite and pyrite in the Nam Quang and Bo Va deposits of the Song Hien basin (Northeast Vietnam) are studied in detail. Arsenopyrite crystals often form elongated crystals. Their chemical composition are relatively poor in As, but rich in S with S/As ratios often > 1.1, impurity elements such as Ni, Co, Sb, and sometimes containing gold (up to 0.02 wt.%). Pyrite is characterized by the stoichiometric composition, but contains relatively high arsenic and sometimes contain gold. The correlation between the concentration of As and Au in pyrite has been recorded. The morphology and chemical composition of arsenopyrite and pyrite of Bo Va and Nam Quang deposits can be correlated to those in the Au-sulfide deposits in black shale in Kazastan and southestern China.ReferencesTrần Trọng Hòa (chủ biên), 1996: Xây dựng mô hình điều tra, sử dụng hợp lý, bảo vệ môi trường trong quá trình khai thác tài nguyên khoáng sản quý hiếm tỉnh Cao Bằng. Lưu trữ Viện Địa chất, Hà Nội. Trần Trọng Hòa, Polyakov G.V., Trần Tuấn Anh, Borisenko A.S., Izokh A.E., Balyakin P.A., Ngô Thị Phượng, Phạm Thị Dung, 2011: Hoạt động magma và sinh khoáng nội mảng miền Bắc Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ, 368tr. Trần Trọng Hòa, Nevolko P., Ngô Thị Phượng, Trần Tuấn Anh, Phạm Thị Dung, Bùi Ấn Niên, Nguyễn Xuân Huyên, Nguyễn Thùy Dương, Vũ Hoàng Ly, Trần Văn Hiếu, 2013: Các tụ khoáng vàng-sulfide trong các thành tạo lục nguyên - carbonat rift Sông Hiến, ÐBVN. Tuyển tập Báo cáo KHCN toàn quốc năm 2013. ISBN: 978-604-59-0693-4; tr.131-140. Nông Thế Tàng (chủ biên), 1996: Báo cáo Khảo sát và tìm kiếm đánh giá vàng gốc Nam Quang, Bảo Lạc, Cao Bằng. Lưu trữ Trung tâm Thông tin lưu trữ Địa chất, Hà Nội. Chen M.H., Mao J.W., Bierlein F.P., Norman T., Uttley P.J., 2011: Structural features and metallogenesis of the Carlin-type Lannigou gold deposit, Guizhou Province, China. OreGeol. Rev.43 (1), 217-234. Fleet, M.E., Mumin, A.H., 1997: Gold-bearing pyrite and arsenopyrite from Carlin Trend gold deposits and laboratory synthesis: American Mineralogist, v. 82, p.182-193. Kovalev K.R., Kalinin Yu.A., Naumov E.A., Kolesnikova M.K., Korolyuk V.N., 2011: Gold-bearing arsenopyrite in eastern Kazakhstan gold-sulfide deposits. Russian Geology and Geophysics 52, 178-192. Kovalev K.R., Kalinin Yu.A., Polynov V.I., Kydyrbekov E.L., Borisenko A.S., Naumov E.A., Netesov M.I., Klimenko A.G., and Kolesnikova M.K., 2012: ISSN 1075-7015, Geology of Ore Deposits, vol. 54, No.4, 254-275. Peters S.G., HuangJ.Z., Li Z.P., JingC.G., 2007: Sedimentary rock-hosted Au deposits of the Dian-Qian-Guiarea, Guizhou, Yunnan Provinces, and Guangxi District, China. Ore Geol. Rev.31,170-204. Volkova A. V., Genkina A. D., and Academician of the RAS Goncharovb V. I., 2006. New data on invisible gold in disseminated sulfide ores of the Natalka deposit. Vol. 409A, No 6, pp. 879-883. Zhong H.R., Chao S.W., Wu B.X., Zhi T.G., Hofstra A.H., 2002: Geology and geochemistry of Carlin- type gold deposits in China Mineralium Deposita 37:378-39. Zhou T.H., Goldfarb R.J., Phillips G.N., 2002: Tectonics and metallogeny of gold deposits in China. Mineralium Deposita 37, 249-282.